ANALISIS KOMPARASI FAKTOR-FAKTOR YANG MEMPENGARUHI LABA SEBELUM PAJAK PADA BANK PEMERINTAH - Vebby Anwar (BJRM (Bongaya Journal of Research in Management), 2018)
The purpose of this study was to determine 1) the image of profit beforetax, net interest margin, loan to deposit ratio, asset quality and operating expenses/ operating income state bank listed on the Indonesia Stock Exchange. 2) analyzethe differences in income before taxes, net interest margin, loan to deposit ratio,asset quality and operating expenses / operating income state bank listed on theIndonesia Stock Exchange. The population in this study are all listed in theGovernment Bank Stock Exchange Bank Indonesia as much as 4. The samplingtechnique used proposive sampling. The analytical method used is descriptive analysis and ANOVA analysisThe results showed that 1) the average profit before tax state bank listed on theIndonesia Stock Exchange the lowest occurred in 2008 and highest in 2011. Theaverage net interest margin is the lowest place in 2011 and highest in 2009. theaverage loan to deposit ratio of the lowest occurred in 2009 and highest in 2011.Average asset quality of the lowest occurred in 2011 and highest in 2009. Averageoperating expenses / operating income of the lowest occurred in 2009 and highestin 2010. 2) There are differences in income before taxes, net interest margin, loanto deposit ratio and the bank's operating expenses/operating incomeintergovernmental listed in Indonesia Stock Exchange in 2008 until 2011. As for thequality of earning assets do not pass the test of homogeneity.